Penerapan Algoritma Outguess dalam Penyembunyian Pesan Pada Citra Berwarna - Yusni Elis Saragih (Bulletin of Computer Science Research, 2022)
The storage or circulation of secret messages is vulnerable to being accessed or wiretapped by parties who do not have legal authority. Therefore, to avoid this and also to secure a secret message known an encryption process called cryptography. In order for the message to be kept confidential, the message is inserted into the image object. Inserting a message in an image or more commonly known as steganography is the development of previously known cryptographic methods. The method with steganography can be said to be better than the previous cryptography. To secure secret messages from unauthorized third parties, steganography is used